Judicial Interpretation of the Inclusion of Standard Clauses in Murabahah Contracts Reviewed from the Principle of Proportionality and Islamic Law - Rezaldy; Nasir, Rifqi Ridlwan; Kusnadi, Egi Hadi (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
Agreements are an important aspect of law relating to business. An agreement basically must fulfill several conditions for the validity of the agreement, as well as paying attention to the legal principles of the agreement. In practice in banking, including Sharia banking, generally agreements or contracts are made using standard clauses. The aim of this research is to find out Juridical interpretation of the inclusion of standard clauses in murabahah contracts in Islamic banks in terms of proportional principles and Islamic law. This research is normative legal research using statutory approaches, legal principles and Islamic law. The results of this research show that the juridical interpretation of the inclusion of standard clauses in murabahah contracts contains elements of a combination of positive law and Islamic law. The inclusion of standard clauses in a murabahah contract must be interpreted contextually, both in terms of the object being traded or the subject matter of the parties involved in the contract.